فعالية استخدام طريقة التحقيق لترقية مهارة الكتابة لدي الطلاب فصل العاشر في المدرسة الثانوية الاسلامية مفتاح الهدى جندونوا - Gustaba Arifin (Universitas Yudharta Pasuruan, 2017)
In learning Arabic includes four components: listening, speaking, reading, and writing. Teaching writing is not an easy thing because the writing skills can be submitted after the students are able to understand other skills, namely listening, speaking, and reading. It takes a high tenacity in teaching it. In addition, the skill of writing is a skill that is quite difficult compared with other skills. The results of the study are summarized as follows 1. The application of the method of inquiry including the good, the result can be seen from the questionnaire is generated from the majority of their students they chose answer A and answer B 41.67 percent to 42.7 percent means that they are very happy using the inquiry method. 2. Using the Inquiry methods known to be effective by looking at the test results as follows then the resulting t or t0 with values ​​of 2.04 degrees 10,647tt 5 percent and this shows a greater than tt t0 is 10,6472,04 then the hypothesis is accepted and Ha Ho null hypothesis is rejected so that it can be concluded in the application method of inquiry is effective in improving Maharah writing in class X MA Miftahul Huda Cendono.